2018
DOI: 10.1088/1755-1315/149/1/012057
|View full text |Cite
|
Sign up to set email alerts
|

Waveform identification and retracking analyses of Jason-2 altimeter satellite data for improving sea surface height estimation in Southern Java Island Waters and Java Sea, Indonesia

Abstract: Abstract. Indonesian waters containing many small islands and shallow waters leads to a less accurate of sea surface height (SSH) estimation from satellite altimetry. Little efforts are also given for the validation of SSH estimation from the satellite in Indonesian waters. The purpose of this research was to identify and retrack waveforms of Jason-2 altimeter satellite data in southern Java island waters and Java Sea using several retrackers and performed improvement percentage analyses for new SSH estimation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 26 publications
1
6
0
Order By: Relevance
“…They were found in near bay and small islands that had shallow waters (<200 m) and were close to the coastline (<17 km). Several studies in other regions reported similar findings, in which the peaky waveforms were found near to the coastline [8,25,29,46,47]. [8] also found that the highest percentage of peaky waveform was onshore, 5-6 km from the coastline.…”
Section: Waveform Classes In Halmahera Seasupporting
confidence: 59%
See 4 more Smart Citations
“…They were found in near bay and small islands that had shallow waters (<200 m) and were close to the coastline (<17 km). Several studies in other regions reported similar findings, in which the peaky waveforms were found near to the coastline [8,25,29,46,47]. [8] also found that the highest percentage of peaky waveform was onshore, 5-6 km from the coastline.…”
Section: Waveform Classes In Halmahera Seasupporting
confidence: 59%
“…Over the Indonesian seas, previous studies (e.g., [23,25,28,29]) reported the performance of several retrackers using the geoidal height data, which highlighting the precision of retracked SSHs. While the accuracy of the retrackers is also valuable, such studies are yet to be done, thus becoming the motivation of this study.…”
Section: Introductionmentioning
confidence: 84%
See 3 more Smart Citations